VD_FINDINFO Jug / 2025 / 249 vom 4. Dezember 2024 - VD Tribunal cantonal (2024)
ACTE D'ORDRE SEXUEL SUR UN INCAPABLE DE DISCERNEMENT, REJET DE LA DEMANDE | 191 CP, 10 CPP (CH), 3 al. 2 let. c CPP (CH)